Subjctive, postoperative judgment of patients pain after certain surgery - Grochans, Elżbieta; Hyrcza, Violetta; Kuczyńska, Magdalena; Szkup-Jabłońska, Małgorzata; Jurczak, Anna; Rotter, Iwona; Zaremba-Pechmann, Liliana; Karakiewicz, Beata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Background : Pain is a natural reaction of an organism when experiencing damage. One problem that modern medicine has to cope with is postoperative pain. According to international and Polish law, patients should be guaranteed pain-free medical care. The pain experienced during the postoperative period can be particularly strong and the ability to estimate it is one of the most important skills of the therapeutic team. Aim of the study : The aim of this study was to analyze the type and intensity of postoperative pain immediately after surgery with regard to different methods of pain assessment, the type and method of a surgical procedure and the type of anaesthesia. Material and methods : The study was conducted from June to September 2009 and involved 84 patients hospitalized at the surgical ward of the Regional Hospital in Kołobrzeg. A diagnostic survey was used and the research instruments included the author’s questionnaire, pain intensity assessment scales and a questionnaire based on the Polish version of the scale of Clinical Quality Indicators in Postoperative Pain Management. Results : The study demonstrated that pain was an integral part of the postoperative period. There was no significant relationship between the method, type of surgery, type of anaesthesia and pain escalation (p > 0.05). According to respondents both pharmacological and non-pharmacological treatment was insufficient. Pain that was experienced on the third day after surgery was significantly weaker than on the first day (p < 0.05). Conclusions: 1. The pain experienced by the patients after surgical procedures was much more intensive on the first than on the third day after surgery. 2. Neither the method and the type of surgery nor the type of anaesthesia had influence on pain intensity. 3. It is necessary to introduce more varied anaelgesic treatment including non-pharmacological methods in the centre.